Conservative fluid resuscitation protocol does not reduce the incidence of reoperation for bleeding after emergency CABG - Bruno, Jowita; Varayath, Mascha; Gahl, Brigitta; Miazza, Jules; Gebhard, Caroline E.; Reuthebuch, Oliver T.; Eckstein, Friedrich S.; Siegemund, Martin; Hollinger, Alexa; Santer, David (Scientific reports, 2024)
Reoperation for bleeding (ROB) after emergency coronary artery bypass grafting (eCABG) has been identified as an independent risk factor for mortality. Consecutively, the influence of fluid intake, fluid output, fluid balance, blood loss, and inotropic demand on ROB were analyzed. This retrospective single-center study included 265 patients undergoing eCABG between 2011 and 2020. From 2018, postoperative hemodynamic management was performed with lower volume administration and higher vasoactive support. The primary outcome measure was the incidence of ROB within 48 h according to altered fluid resuscitation strategy. Consecutively, the influence of fluid intake, fluid output, fluid balance, blood loss, and inotropic demand on ROB were analyzed. Incidence of ROB was independent from the volume resuscitation protocol ( P = .3). The ROB group had a higher perioperative risk, which was observed in EuroSCORE II. Fluid intake ( P = .021), fluid balance ( P = .001), and norepinephrine administration ( P = .004) were associated with ROB. Fluid output and blood loss were not associated with ROB ( P = .22). Post-test probability was low among all variables. Although fluid management might have an impact on specific postoperative complications, different fluid resuscitation protocols did not alter the incidence of ROB after emergency CABG. Trial registration: www.clinicaltrials.gov registration number NCT04533698; date of registration: August 31, 2020 (retrospectively registered due to nature of the study); URL: https://classic.clinicaltrials.gov/ct2/show/NCT04533698